The “yellow vests” movement in France: problems, causes, prospects - L. D. Efanova (Управление)
The “yellow vests” protest movement began in France at the end of 2018. These protests are the most widespread in the country since 1968. The causes of the emergence of the “yellow vests” movement and the dynamics of the involvement in them of representatives of various regions of France have been considered in the article. Initially, the protesters expressed disagreement with the increase in taxes on fuel as a claim against the French government. Gradually, the requirements expanded more and more, acquiring political overtones.Most of the population began to live worse due to lower incomes. The rating of the French President E. Macron has fallen markedly since his inauguration, and the support of the country’s population has declined significantly. During his presidency, tax breaks mainly affected only large businesses. The poor people were disadvantaged due to the reduction of social payments, as well as an increase in direct and indirect taxes.The main reasons of occurence of the “yellow vests” movement are the dissatisfaction of the French with their economic position and the decline in the living standards. The article notes, that this movement has gone beyond the borders of France, covering other Western European countries such as Belgium, Spain, Italy, Germany, Sweden, which are experiencing similar problems. The main differences of this protest movement from those, that happened in France before, have been considered in the article. The economic and political demands, that were put forward by the protesters to their government and President E. Macron have been presented. The prospects for the development of the “yellow vests” movement in modern France have been considered.